Iklan Kosmetik Bayi dalam Mediamassa Cetak Struktur Wacana, Analisis Kritis Interaksi Sosial, dan Unsur-unsur Direktif Sebuah Pendekatan Sosiolinguistik Baby Cosmetic Advertisements in the Printed Mass Media - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 2003)
This study entitles "Baby Cosmetic Advertisements in The Printed Mass Media": Discourse Structure, Critical Analysis on Social Interaction, and Directive Elements. It is a descriptive-qualitative research. The analysis focuses on 1) discourse structure, 2) social interaction, and 3) directive languages constructing baby cosmetic advertisements. The data are words, phrases, clauses, sentences, and discourse of baby cosmetic advertisements. The data are taken from Nova, Nakita, Bunda, Ibu Anak, Femina, and Ayah Bunda published in 2001. The choice of the data is merely due to the time of the study. The first four are tabloid. The rest are magazines. The technique of collecting data is purposive sampling. It means that this study aims at describing the specific aspect in the discourse of baby cosmetic advertisements. Therefore, the writer classifies the data based on the manufacturer of the product